Astringency sub-qualities drying and pucker are driven by tannin and pH – Insights from sensory and tribology of a model wine system. (December 2020) - Wang, Shaoyang; Olarte Mantilla, Sandra M.; Smith, Paul A.; Stokes, Jason R.; Smyth, Heather E.
Abstract: Astringency mouthfeel is an important indicator of wine sensory quality that has been associated with colloidal interactions between tannins and salivary proteins, and a depletion in the lubricating salivary film. However, astringency is a complex sensation that has several contributing sub-qualities that may each have different physicochemical origins. We find that the model wine sample set varying in tannin, pH and polysaccharide content exhibit variations in the main sub-qualities: drying, rough and pucker . A range of soft-tribological methods involving saliva are used to gain mechanistic insight into these sub-qualities. Results suggest that rough is a secondary sub-quality that can be elicited by either drying or pucker, while these two sensations are driven by high tannin and low pH, respectively. Samples with 'chemically-equalised' astringency, which have similar colloidal stability upon interaction with saliva (saliva precipitation index), are also found to have varying sub-qualities and tribological responses. The boundary friction of saliva-wine mixtures in Stribeck curve aligned with drying, and the rate of increase in boundary friction of a salivary pellicle upon contacting wine aligned with pucker . Rough is not found to scale with any physical measure we explored. Quartz crystal microbalance indicated that the tannin, rather than pH, interacts with the salivary protein film to cause an increase in surfaces adsorbed mass in the absence of significant shear. The results indicate that while tannin and acid both contribute to the perception of astringency, the mechanisms by which they do this have different origins that lead to differences in sub-qualities. Graphical abstract: Image 1 Highlights: Samples with chemically-equalised astringency exhibited different sub-qualities. Rough is a secondary sub-quality elicited by either drying or pucker . Higher tribology boundary friction associated with high tannin is linked to drying . Lower pH linked to pucker and a faster collapse of salivary pellicle in tribology. Higher tannin increased adsorbed mass on the salivary film in QCM-D.